2013
DOI: 10.1371/journal.pone.0081572
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulation of Endoplasmic Reticulum Stress Markers in Prostate Cancer Cells by a Standardized Mangosteen Fruit Extract

Abstract: The increased proliferation of cancer cells is directly dependent on the increased activity of the endoplasmic reticulum (ER) machinery which is responsible for protein folding, assembly, and transport. In fact, it is so critical that perturbations in the endoplasmic reticulum can lead to apoptosis. This carefully regulated organelle represents a unique target of cancer cells while sparing healthy cells. In this study, a standardized mangosteen fruit extract (MFE) was evaluated for modulating ER stress protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Although significant medical and technological developments have been achieved, still conventional cancer-targeted therapies have severe side effects and complications such as serious toxicities and development of resistance [ 161 , 162 ]. Therefore, one of the major goals for cancer treatment is to find novel therapeutic approaches which make it possible to selectively kill cancer cells without harming normal cells and reduce cancer cellular resistance to chemotherapeutic agents [ 145 , 147 , 158 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although significant medical and technological developments have been achieved, still conventional cancer-targeted therapies have severe side effects and complications such as serious toxicities and development of resistance [ 161 , 162 ]. Therefore, one of the major goals for cancer treatment is to find novel therapeutic approaches which make it possible to selectively kill cancer cells without harming normal cells and reduce cancer cellular resistance to chemotherapeutic agents [ 145 , 147 , 158 , 163 ].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis in PNT1a and PC3 cells through CHOP expression, triggering BH3-only proteins, AIF and cleavage of caspase-3,-9 was demonstrated by the treatment of Polyphenol E (derived from Camellia sinensis ) [ 144 ]. Mangosteen Fruit Extract (MFE; derived from Garcinia mangostana ) enhanced the level of PERK, CHOP, IRE1 and caspase-4 in both LNCaP and 22Rv1 cells through ER stress, leading to Bax and cleavage of caspase-3 [ 145 ]. Upregulation of eIF2α-ATF4-CHOP signaling and caspase-4 in PC-3, DU145, and LNCaP cells through ER stress was observed after treatment of Marchantin M (Mar; derived from Astrella angusta ) [ 146 ].…”
Section: Anti-cancer Effects Of Natural Products Via Er Stressmentioning
confidence: 99%
“…When UPR is unable to cope with the increased protein demand, ER stress is prolonged, and cell apoptosis is initiated. Recently, we have reported that a standardized mangosteen extract modulated the UPR pathway in prostate cancer cells . In that particular study we identified up to 26 different xanthones including gartanin in mangosteen extract.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, ER stress has been regarded as the third apoptotic pathway. α-MG was found to selectively promote ER stress so as to increase the apoptotic indices of prostate cancer cells, while exerting little influence on normal prostate epithelial cells [96,97].…”
Section: Induction Of Apoptosismentioning
confidence: 99%